2012
DOI: 10.1177/0734016812465745
|View full text |Cite
|
Sign up to set email alerts
|

Do Women and Men Differ in Their Neutralizations of Corporate Crime?

Abstract: Neutralization theory has commonly been used to understand the motivations of street offending, and recent studies have examined the use of neutralization techniques by corporate and white-collar offenders to account for their crimes. However, few researchers have explored whether this process is gendered. Using data from master of business administration (MBA) students, this study examines how gender influences intentions to inhibit or promote the sale of Panalba, a hypothetical pharmaceutical drug known to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Indeed, a small body of research emerged in the 1980s to develop the concept of techniques of neutralization to corporate wrongdoing: the illegitimate activities that corporation engages in [12,13,14]. More recently there has been a resurgence of research that has applied this basic approach to corporate wrongdoing ( [15,16,17]; and [18]). This work uses precisely the same framework set out by Sykes and Matza and followed by Cohen (though remarkably, Cohen refers to none of this work on corporate denial in his work on state denial; 1993 and 2001).…”
Section: Corporate Techniques Of Neutralizationmentioning
confidence: 99%
“…Indeed, a small body of research emerged in the 1980s to develop the concept of techniques of neutralization to corporate wrongdoing: the illegitimate activities that corporation engages in [12,13,14]. More recently there has been a resurgence of research that has applied this basic approach to corporate wrongdoing ( [15,16,17]; and [18]). This work uses precisely the same framework set out by Sykes and Matza and followed by Cohen (though remarkably, Cohen refers to none of this work on corporate denial in his work on state denial; 1993 and 2001).…”
Section: Corporate Techniques Of Neutralizationmentioning
confidence: 99%
“…There are however a number of criminological studies that are of relevance to the current research. A number of scholars have studied how individuals employ different types of neutralisation techniques in order to motivate white-collar crime [20,21]. These studies differ from the current paper however, in that they focus on processes associated with the individual offender.…”
Section: Previous Researchmentioning
confidence: 48%
“…Finally, it should also be noted that much of the sex differences may be due to the measure of MD more generally. Research on the neutralizations reported by offenders suggests that men and women differ in the extent that they neutralize (which is supported here) and in the specific excuses that they provide (Klenowski et al, 2011;Vieraitis, Piquero, Piquero, Tibbetts, & Blankenship, 2012). It is possible that our MD scale is weighted toward those MDs most often used by men.…”
Section: Discussionmentioning
confidence: 82%